Gill amoebae from freshwater rainbow trout (Oncorhynchus mykiss) In vitro evaluation of antiparasitic compounds against Vannella sp - Jensen, Hannah Malene (Journal of fish diseases, 2020)
© 2020 John Wiley & Sons Ltd.